2023
DOI: 10.1098/rsta.2023.0132
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of social distancing measures and lockdowns for reducing transmission of COVID-19 in non-healthcare, community-based settings

Caitriona Murphy,
Wey Wen Lim,
Cathal Mills
et al.

Abstract: Social distancing measures (SDMs) are community-level interventions that aim to reduce person-to-person contacts in the community. SDMs were a major part of the responses first to contain, then to mitigate, the spread of SARS-CoV-2 in the community. Common SDMs included limiting the size of gatherings, closing schools and/or workplaces, implementing work-from-home arrangements, or more stringent restrictions such as lockdowns. This systematic review summarized the evidence for the effectiveness of nine SDMs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 309 publications
1
9
0
Order By: Relevance
“…The effect of NPIs is consistent across each model variant we consider. The association between NPIs and logR t are consistent with the broader literature [ 20 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of NPIs is consistent across each model variant we consider. The association between NPIs and logR t are consistent with the broader literature [ 20 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…The Royal Society recently conducted a series of reviews looking at the efficacy of nonpharmaceutical interventions during COVID-19, which suggested that social distancing measures can be highly effective in mitigating the risk of contagion within a population [18]. Environmental controls may also be advantageous, though more focused research is required in that regard [28].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst people have good intentions, these might not always be followed by good actions. Indeed, a recent review of the efficacy of lockdowns (or 'stay-at-home' orders) and other social-gathering regulations, acknowledged that adherence was a critical but understudied factor in efficacy [18]. Challenges to adherence have been evidenced by one of very few behavioral observational studies that looked at COVID-19 transmission [19].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic crisis has caused great unrest in society and unprecedented changes in lifestyle, work, and social interactions [ 48 ]. The implementation of policies such as social distancing and the closure of gathering and interaction centers such as parks, cafes, schools, universities, etc., has had certain social consequences [ 49 ]. The adoption of smart work modalities by many industries and institutions may have exerted deleterious effect on health outcomes according to the results of a recently published paper which has demonstrated that after adjusting for sex, age, education, smoking, drinking, and body mass index, individuals who mostly sat at work had a 16% higher all-cause mortality risk, and a 34% increased mortality risk from cardiovascular disease compared with those who were mostly non-sitting at work [ 50 ], although the prevalence of arterial hypertension remained unchanged.…”
Section: Discussionmentioning
confidence: 99%